AGILITY AS A MODERN FORM OF RECREATION - Monika Niewiadomska (Physical Education of Students)
Physical activity is one of the main factors to influence human health. The beneficial effects of physical exercise and various forms of active recreation can only be observed, however, after systematic application, which usually occurs when exercise is in line with one's interests and preferences. The increasing number of forms of recreation makes it possible to customize these to suit individual needs. One such recreational activity is agility , i.e. keeping pace with a dog through an obstacle course while leading the dog through the various obstacles in certain ways. The main purpose of the presenting work was to analyze agility’s impact as therapeutic effects on the people of all ages, including children. Currently, agility is developing as a sport and a form of recreation in Poland and over the world. Due to its versatility, agility is suitable for people of all ages. It is a spectator sport, enjoying growing interest among children, adolescents and adults. This form of physical recreation, next to the positive impact on the physical development, also has a considerable positive impact on the human psyche.